2012
DOI: 10.3390/ijms13032846
|View full text |Cite
|
Sign up to set email alerts
|

Astragalin from Cassia alata Induces DNA Adducts in Vitro and Repairable DNA Damage in the Yeast Saccharomyces cerevisiae

Abstract: Reverse phase-solid phase extraction from Cassia alata leaves (CaRP) was used to obtain a refined extract. Higher than wild-type sensitivity to CaRP was exhibited by 16 haploid Saccharomyces cerevisiae mutants with defects in DNA repair and membrane transport. CaRP had a strong DPPH free radical scavenging activity with an IC50 value of 2.27 μg mL−1 and showed no pro-oxidant activity in yeast. CaRP compounds were separated by HPLC and the three major components were shown to bind to DNA in vitro. The major HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…Media and solutions were prepared [31,32]. Complete liquid medium (YPD -1.0% yeast extract, 2.0% polypeptone, 2.0% glucose, pH 5.3) was used for routine growth of yeast cells.…”
Section: Strains and Mediamentioning
confidence: 99%
“…Media and solutions were prepared [31,32]. Complete liquid medium (YPD -1.0% yeast extract, 2.0% polypeptone, 2.0% glucose, pH 5.3) was used for routine growth of yeast cells.…”
Section: Strains and Mediamentioning
confidence: 99%
“…Moreover, AECal could have acted as reactive species quenchers. In fact, several studies reported the free radical scavenging ability in Cassia alata extracts [23–26]. AECal - induced synthesis of antioxidant enzymes and inhibition/stimulation of specific proteins involved in DNA damage repair remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Preparative HPLC of ethyl acetate phase (fraction B) indicated the presence of kaempferol 3-O-β-glucoside (astragalin) as the major glycoside and isolated it by comparison with reported retention time in literature [13]. Fig.…”
Section: Isolation Of Kaempferol 3-o-β-glucoside (Astragalin)mentioning
confidence: 98%